Parenting Style and Anxiety Symptoms A Moderated-Mediation Analysis of Interpersonal Cognitive Distortions and Anxiety Disorder - Burcu Buge; Volkan Koc (Yaşam Becerileri Psikoloji Dergisi)
Anxiety symptoms often relate to perceived negative parenting styles inherited from one's parents, impacting cognitive processes in interpersonal relationships. This study investigates the association between anxiety symptoms, parenting styles, and interpersonal cognitive distortions in individuals with anxiety disorders compared to healthy controls. The study involved 164 adult participants—82 with diagnosed anxiety disorders and 82 without psychiatric diagnoses, comprising 42 (26%) males and 122 (74%) females, aged 18-60 years (mean age = 30.5±8.84). Participants completed a demographic questionnaire, the Young Parenting Inventory, the Interpersonal Cognitive Distortions Scale, and the Beck Anxiety Inventory. The anxiety disorder group exhibited heightened levels of anxiety symptoms, interpersonal cognitive distortions, and specific maternal parenting styles (overprotective/unbounded, conditional/achievement-oriented, and pessimistic/anxious), as well as a paternal resistant/suppressive parenting style, in contrast to the control group. Interpersonal cognitive distortions were identified as mediators in the relationships between overprotective/unbounded maternal parenting and anxiety, as well as closed to change/repressing paternal parenting and anxiety. However, the diagnosis of anxiety disorder did not moderate the relationship between parenting styles and cognitive distortions. These findings emphasize the importance of targeting interpersonal cognition in treating and preventing anxiety disorders, especially in individuals with overprotective/unbounded mothers and resistant/suppressive fathers.